To the question of interaction of related scientific disciplines in the formation of multidisciplinary terminology system CLIMATE CHANGE - A. I. Laptinova (Вестник Самарского университета: История, педагогика, филология)
The article is devoted to the analysis of terminology of the subject area Climate Change, in order to determine its belonging to the interdisciplinary or multidisciplinary type. The article examines the nature of interaction of the terminology of Climate Change with the terminological systems of disciplines included in the analyzed subject area. Particular attention is paid to the processes of conceptualization and resemantization of terms, their transformation during integration into a new area of knowledge - cumulative and integrative changes reflected in the terminological system. It was revealed that at the level of general terms, the terminology of Climate Change demonstrates interdisciplinarity, while at the level of specific terms, the multidisciplinary nature prevails, due to the anthropocentric and anthropogenic specificity of the conceptual sphere of Climate Change. The work focuses on the key conceptual features of the terminology of Climate Change, such as popularization, risks, threats, as well as its impact on the social and humanitarian areas of knowledge, which allows us to classify this area as an actively developing multidisciplinary system